MANAJEMEN PENDIDIKAN ISLAM DALAM PENINGKATAN KEDISIPLINAN PESERTA DIDIK DI SEKOLAH SMPIT INSAN MANDIRI BOARDING SCHOOL PARUNG BOGOR TAHUN AKADEMIK 2024-2025 - ELIYA MARLIZA; AN AN ANDARI; TOHA MA'ARIF (UNISAN JURNAL, 2025)
The background of this research is the world of education which is experiencing quite heavy tests and challenges. One of them is the occurrence of a decline in the values of the character of discipline marked by the presence of students who are truant during class hours and are late for school. First, how is the process of disciplinary character education for students at PKBM Imam, Taman Subdistrict Sidoarjo Regency. Second, how are the results of student discipline character education at PKBM Imam Muslim Islamic School, Taman Subdistrict, Sidoarjo Regency. The type of research used is a qualitative field research type. The data collection is by observation, interview and documentation methods. The results showed that the process of disciplinary character education of students at PKBM Imam Muslim Islamic School Taman Subdistrict, Sidoarjo Regency by: (1) First, habituation through muhasabah and khuruj. Second, teach good things, Third, through Bayan and Taklim in the implementation of khuruj activities, so that they feel and love the good. Fourth, through good practices. Fifth, by example, through muhasabah and khuruj activities. Sixth, tarbiyah, (2) The results of disciplinary character education at PKBM Imam Muslim Islamic School, Taman Subdistrict, Sidoarjo Regency are very good, in this case by showing an increase in student behavior in terms of worship and learning.